Pengaruh Kebijakan Pemerintah dan Peran Serta Masyarakat terhadap Kualitas Lingkungan Pesisir Benoa Badung Bali - Suryani, Anih Sri (Jurnal Aspirasi, 2019)
Management of coastal and coastline is very important in Indonesia, an archipelago country with the longest coastline in the world. Moreover, conditions in some coastal areas in Indonesia have decreased the environment quality for example in the Benoa Region of Bali. This paper aims to quantify the influence of government policies and community participation on the quality of the coastal environment in Benoa Badung Bali Region in the perspective of sustainable development. The quantitative method with the questionnaire instrument was carried out in this study. The results showed that the size of the index for government policy in the Benoa Region was 67.45 (sufficient), the community participation index 78.06 (good), the water condition index 72.78 (good) and the land condition index 74.62 (good). Statistical analysis shows that there is a significant relationship between government policy and community participation in the quality of the coastal and coastal environment (r=0,541). Government policies and community participation have  positive effect on the condition of the quality of the coastal and coastal environment. Various community empowerment activities and programs and government policies in the Benoa Region, for example the Yasa Segara Pokmaswas group, the development of conservation tourism in Badung, fisheries business development have fulfilled the principles of sustainable development in terms of economic, social/community participation and the environment.AbtrakPengelolaan pesisir dan pantai sangat penting di Indonesia yang merupakan daerah kepulauan dengan garis pantai terpanjang di dunia. Terlebih kondisi di sebagian pesisir di Indonesia kualitas lingkungannya menurun seperti di Kawasan Benoa Badung Bali. Tulisan ini bertujuan untuk menghitung pengaruh kebijakan pemerintah dan peran serta masyarakat terhadap kualitas lingkungan pesisir di Kawasan Benoa Badung Bali. Metode kuantitatif dengan instrumen kuesioner dilakukan dalam penelitian ini. Hasil penelitian menunjukan bahwa besaran indeks untuk kebijakan pemerintah di Kawasan Benoa adalah 67,45 (cukup), indeks peran serta masyarakat 78,06 (baik), indeks kondisi perairan 72,78 (baik) dan indeks kondisi daratan 74,62 (baik). Analisis statistik menunjukkan bahwa terdapat hubungan yang signifikan antara kebijakan pemerintah dan peran serta masyarakat terhadap kualitas lingkungan pesisir dan pantai (r=0,541). Kebijakan pemerintah dan peran serta masyarakat berpengaruh positif terhadap kondisi kualitas lingkungan pesisir dan pantai. Berbagai kegiatan dan program pemberdayaan masyarakat dan kebijakan pemerintah di Kawasan Benoa misalnya adanya kelompok Pokmaswas Yasa Segara, pengembangan wisata konservasi di Badung, pengembangan usaha perikanan telah memenuhi prinsip-prinsip pembangunan pesisir secara terpadu dan berkelanjutan.